A systematic review of questionnaires used to measure the time spent on family care for frail older people. (23rd June 2017) - Cès, Sophie; De Almeida Mello, Johanna; Macq, Jean; Van Durme, Thérèse; Declercq, Anja; Schmitz, Olivier
Abstract : Time spent on family care of frail older people is difficult to substantiate because of its complex nature. The aim of this study is to check the content validity of existing questionnaires measuring the time spent on caring. Comparing the activities mentioned in the questionnaires with those from other data sources (three validated scales measuring the functional limitations in day-to-day activities and a qualitative study) enabled identification of important drawbacks in the questionnaires reviewed. A comprehensive list of activities was built in order to help future researchers to conduct effective data collection and thereby enable an in-depth analysis of family care supply.